2013
DOI: 10.1002/lary.24037
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory functions after transsphenoidal pituitary surgery: Endoscopic versus microscopic approach

Abstract: This is the first study to seek the difference between the endoscopic and microscopic transsphenoidal approaches on the olfactory system during pituitary surgery. The obtained results indicate that an endoscopic approach seems to be more advantageous than a microscopic approach for protecting olfactory system and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 53 publications
1
60
1
Order By: Relevance
“…Additionally, the questionnaires at 2 and 4 weeks were completed by telephone, which may have led to a different response than the paper-based surveys. Nonetheless, our total sample size at all time points is similar to those in other studies that have measured QOL, 19 headache, 18 and sinonasal function 17,20,27 after transsphenoidal surgery. Additionally, the sample size is similar to those in other studies that have provided comparative analyses of QOL 19 and nasal function 17 between microscopic and endoscopic techniques.…”
Section: Study Advantages and Limitationsmentioning
confidence: 66%
See 2 more Smart Citations
“…Additionally, the questionnaires at 2 and 4 weeks were completed by telephone, which may have led to a different response than the paper-based surveys. Nonetheless, our total sample size at all time points is similar to those in other studies that have measured QOL, 19 headache, 18 and sinonasal function 17,20,27 after transsphenoidal surgery. Additionally, the sample size is similar to those in other studies that have provided comparative analyses of QOL 19 and nasal function 17 between microscopic and endoscopic techniques.…”
Section: Study Advantages and Limitationsmentioning
confidence: 66%
“…In a study utilizing the sense of smell, Kahilogullari and colleagues found, through the use of the Smell Diskettes Olfaction Test, that the endoscope was more effective than the microscope in preserving olfactory function up to 6 months after surgery. 17 Although these added items would affect the total of the SNOT and NOSE construct scores, the addition of olfactory items would probably not affect the overall trend of our data given our specific analysis of the individual NOSE components and SNOT-20 subscales.…”
Section: Nasal and Nasal-related Qol Progressionmentioning
confidence: 94%
See 1 more Smart Citation
“…1,6 Ultimately, this mucosal trauma is dictated by differences in surgical technique, even among procedures described under the umbrella term endonasal endoscopic approach" However, the design of the nasoseptal flap has not been well addressed, and it is likely that heterogeneous practices exist. Authors have suggested modifications to the technique, 1,17 and the data presented in this study provide evidence that preservation of the olfactory strip as a discrete area can avoid significant impact on both olfaction and sinonasal function.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] In general, patients prefer the endoscopic approach, 5 and olfactory scores are better after the endoscopic route. 6 The nasoseptal flap, in particular, to reconstruct the skull base as part of the overall process has been implicated in smell dysfunction. However, much of the literature on the impact of the nasoseptal flap comes from extended skull base surgery.…”
mentioning
confidence: 99%